T3 Sema3F is an autocrine neutrophil retention signal regulating neutrophil transit and effector functions in acute lung injury. (December 2018) - Plant, TM; Carlin, L; Ellett, FEJ; Mirchandani, A; Morgan, JM; Watts, E; Murphy, F; Eamsamnarng, S; Furley, A; Whyte, MKB; Walmsley, S
Abstract : Effective host responses to injury and infection require both rapid recruitment of neutrophils into tissues and timely inflammation resolution. Research currently focuses on initiation and resolution as distinct phases of inflammation and neutrophil survival as a key determinant of the inflammatory response. Less focus has been placed on mechanisms retaining viable neutrophils at inflamed sites and thus contributing to ongoing inflammation. This may be of therapeutic importance given the numerical dominance of viable over apoptotic neutrophils in inflamed tissue, even during inflammation resolution. Semaphorins are proteins that regulate motility in a variety of cell types and systems. We observed that neutrophils regulate Sema3F transcript abundance, which is expressed in the airway myeloid cell population of COPD patients. We then questioned whether Sema3F could regulate neutrophil migration and define the magnitude of the inflammatory response. Not only do inflammatory neutrophils express the class 3 Semaphorin, Sema3F and its obligatory co-receptor Neuropilin 2 (NRP2) but expression of both is further induced by bacterial Lipopolysaccharide (LPS) and other inflammatory stimuli. In a murine model of LPS-induced acute lung injury, we describe a phenotype where neutrophil specific knockdown of Sema3F both increases neutrophil recruitment to the airways 6 hours following LPS challenge (***p=0.0079, n=9) and enhances the rate of inflammation resolution (wild-type airway neutrophil count T50 =42 hours, Sema3F knockout T50 =32.9 hours). Conversely, intra-tracheal instillation of Sema3F in wild-type mice retains neutrophils at the injury site following maximal recruitment (p=0.046, n=8). In vitro experiments using human neutrophils demonstrate Sema3F reduces neutrophil chemotaxis producing 'rounder cells', phagocytosis is unaffected but interestingly respiratory burst is enhanced (*p=0.0117, n=3). Using confocal microscopy and image analysis software we identified the location of the neutrophils in the murine lung interstitium following LPS induced lung injury. We show that intra-tracheal Sema3F holds the recruited neutrophils in the alveolar space (*p<0.0001, n=11). In vivo Sema3F induces neutrophil F-actin disassembly (**p=0.089, n=8) thus promoting neutrophil retention. Taken together these data suggest that Sema3F acts as a migratory 'brake', so that ligand and co-receptor (NRP2) could provide novel therapeutic targets for the modulation of pathological neutrophilic inflammation in respiratory disease.